Improving Students’ Achievement In Writing Analytical Exposition Paragraph Through Debate Technique - Olanda Theresia Sianturi (Universitas Negeri Medan, 2012)
The objective of this research is to find out the effectiveness of the implemantation of debate technique in order to improve students’ achievement in writing analytical exposition paragraph. The study was conducted by using class room action research. The subject of this study was the second year students of SMA Santo Thomas 4 Binjai consisting of 25 students. The study was implemented in two cycles and each cycle consisted of three meetings. The instruments of data collection were writing test and social judgement (diary notes, observation sheets, questionnaire, and interview). The research result in that 1) the implementation of debate technique is effective to improve students’ achievement in writing analytical exposition paragraph which is in writing test result, students’ scores kept improving in every test that In orientation the mean score was 28,8, in the test of cycle I 51,8 and in the test of second cycle was 65. It means there is a significant improvement toward the before, after, during several times of the aplication, 2) students’ perception on debate technique is good and positive, 3) and the teaching – learning process run well That students were active and enthusiastic in writing. Key Word: Debate, Analytical Exposition, Improving